INDICADORES INTERNOS E EXTERNOS PARA ESTIMATIVA DA DIGESTIBILIDADE APARENTE DA MATÉRIA SECA EM OVINOS - MATOS, Romário Ferreira de (2017)
The objective of this study was to evaluate the accuracy and precision of the apparent dry matter digestibility estimates obtained using internal and external markers in sheep fed diets containing sugar-cane-tip hay or treated with urea or calcium. Also, it was evaluated the robustness of the markers in relation to the variation of dry matter intake (CMS) and the mean live weight (PV) of the animals. Were used 20 male, uncastrated, mestizos without defined breed pattern (SPRD) x Santa Inês, with a mean live weight of 29.64 ± 5.53 kg and age of approximately 12 months, in randomized block design, based on live weight. Estimates of total fecal dry matter yield and digestibility of DM and nutrients were performed using the method of total fecal collection and using internal markers, represented by the indigestible constituents MSi, FDNi and FDAi and the external indicator titanium dioxide (TiO2). Accuracy of the markers was evaluated by the mean bias, which is the difference between the value predicted by the indicator and the value observed by the total collection of feces, the most accurate indicator being considered, which presents a mean bias closer to zero. Precision, a measure of dispersion between predicted and observed values, represents the mean distance variability between these values and was evaluated by the mean square root of the prediction error. The robustness analysis of each indicator was performed by regressing the bias according to the CMS variables and PV. TiO2 presented a faecal recovery rate (TRF) of less than 100% and for the internal markers MSi, FDNi and FDAi. TRF was greater than 100%. There was a difference for the mean bias (P <0.05), which shows that there are differences in the markers regarding their accuracy for fecal yield estimates and, consequently, estimates of apparent dry matter digestibility (DMS) in sheep. The estimated of digestibility of dry matter (DMS) for internal markers MSi, FDNi and FDAi are recommended because the results obtained by these are not influenced by the CMS and PV.